From culture to innovate product : batik design in porcelain wares / Nurul ‘Ayn Ahmad Sayuti ... [et al.] - Nurul ‘Ayn, Ahmad Sayuti; Mas Ayu, Zainal @Ismail; Ahmad Fazlan, Ahmad Zamri; Mohd Zamri, Azizan (Universiti Teknologi MARA, Perak, 2018)
In this paper, the Batik Merbok motifs are proposed to be used in porcelain wares using 3D (CAD) software. The natural motifs developed are seen to have potential to be incorporated in tableware collections or as a daily home-product usage. It is a conceptual paper which explaining the motifs developed by Batik Merbok and discussing the 3D (CAD) design developments. The motifs were developed with a combination of flora, fauna and the humanmade historical artefacts which were inspired from the surrounding areas of Merbok, Kedah. A detail research results are not yet conclusive; therefore, the researchers will continue to develop the porcelain wares further and investigate the consumer perceptions towards the incorporation of the batik motifs. It is one of the sole efforts of bringing Batik Merbok into exploring another genre of designs.